2012
DOI: 10.1007/s10508-012-9925-7
|View full text |Cite
|
Sign up to set email alerts
|

Feederism: An Exaggeration of a Normative Mate Selection Preference?

Abstract: Quinsey and Lalumière (1995) suggested that some, if not most, paraphilias are exaggerated manifestations of more normative and functional mate selection preferences. The present study tested whether Feederism, a fat fetish focused on erotic eating, feeding, and gaining weight, is an exaggeration of a sexual arousal pattern commonly seen in the general population. Thirty participants (15 men and 15 women) recruited from the general population were assessed using penile plethysmography and vaginal photoplethysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Most studies reporting discordance in women find a pattern opposite to what was found in the current study, in that there is usually an absence of subjective sexual arousal in the presence of a genital response (Chivers & Bailey, 2005; Chivers et al, 2004; Suschinsky & Lalumière, 2011a, 2011b). One study has reported a direction of discordance similar to what was found in the current study, in that men and women reported being sexually aroused (to scenarios involving feeding) in the absence of a genital response (Terry, Suschinsky, Lalumière, & Vasey, 2012), suggesting that these two responses may be controlled by different pathways or systems.…”
Section: Discussionsupporting
confidence: 78%
“…Most studies reporting discordance in women find a pattern opposite to what was found in the current study, in that there is usually an absence of subjective sexual arousal in the presence of a genital response (Chivers & Bailey, 2005; Chivers et al, 2004; Suschinsky & Lalumière, 2011a, 2011b). One study has reported a direction of discordance similar to what was found in the current study, in that men and women reported being sexually aroused (to scenarios involving feeding) in the absence of a genital response (Terry, Suschinsky, Lalumière, & Vasey, 2012), suggesting that these two responses may be controlled by different pathways or systems.…”
Section: Discussionsupporting
confidence: 78%
“…In fact, some individuals may combine sexual and eating gratifications and form a unique type of fantasy (i.e., feederism). In one study, men and women from general population who were shown neutral and feeding still images while listening to audio recordings of neutral and feeding stories subjectively rated feeding stimuli as more sexually arousing than neutral stimuli (Terry et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, people who engage in varying types of BDSM (bondage, dominance, sadism, masochism) can do so within a framework of behavior, identity (e.g., kink-identified, in the lifestyle), and orientation (being drawn to this partnered sexuality over or alongside others) (Kleinplatz & Diamond, 2014;Terry, Suschinsky, Lalumiere, & Vasey, 2012;Terry & Vasey, 2011;Weiss, 2011). Becoming excited or drawn to themes of exhibitionism, risky sex, voyeurism, or other kinkrelated sexualities could be anotheriteration ofsexualparameter n .…”
Section: Parameter 4: Sexual Parameter N Sexualitymentioning
confidence: 99%